(untitled) (Journal of Nobel Medical College, 2025)
Background: Anxiety and depression are prevalent mental health illness that can affect anyone but most common seen in the medical students. This study finds the prevalence and associated risk factor of anxiety and depression among the medical students. Materials and Methods: A cross section descriptive study conducted among the 187 medical students of first and third year bachelor of medicine and bachelor of surgery enrolled in Nobel Medical College Teaching Hospital using Beck anxiety and depression inventory with questionnaire. Whole sampling was done and study conducted between May and June 2025. Results: Prevalence of anxiety and depression was 29.6% (55) and 58.8% (110) respectively. The prevalence of anxiety in male was 12.9% (12) and depression 53.8% (50). Similarly, the prevalence of anxiety in female was 45.7% (43) and depression 63.8% (60) respectively. Conclusion: This study finds the prevalence of anxiety and depression among the medical students who study bachelor of medicine and bachelor of surgery. The prevalence of anxiety and depression were more in female, those students with insufficient pocket money and substance abuse.